Bioreactor-based advances in plant tissue and cell culture: challenges and prospects. (2nd January 2019) - Valdiani, Alireza; Hansen, Ole Kim; Nielsen, Ulrik Braüner; Johannsen, Vivian Kvist; Shariat, Maryam; Georgiev, Milen I.; Omidvar, Vahid; Ebrahimi, Mortaza; Tavakoli Dinanai, Elham; Abiri, Rambod
Abstract: Bioreactors are engineered systems capable of supporting a biologically active situation for conducting aerobic or anaerobic biochemical processes. Stability, operational ease, improved nutrient uptake capacity, time- and cost-effectiveness, and large quantities of biomass production, make bioreactors suitable alternatives to conventional plant tissue and cell culture (PTCC) methods. Bioreactors are employed in a wide range of plant research, and have evolved over time. Such technological progress, has led to remarkable achievements in the field of PTCC. Since the classification of bioreactors has been extensively reviewed in numerous reviews, the current article avoids repeating the same material. Alternatively, it aims to highlight the principal advances in the bioreactor hardware s used in PTCC rather than classical categorization. Furthermore, our review summarizes the most significant steps as well as current state-of-the-art of PTCC carried out in various types of bioreactor.